KARAKTERISTIK IKLIM DAN TANAH VULKANIS DI SISI BARAT GUNUNG API IJEN JAWA TIMUR SEBAGAI DASAR PENENTU PENGELOLAAN VARIETAS TANAMAN PADI (Oriza sativa L.) - Basuki Basuki; Sukron Romadhona; Vega Kartika Sari; Iqbal Erdiansyah (Jurnal Penelitian Pertanian Terapan, 2021)
The suitability of typical rice varieties in Tegalampel Sub-District, Bondowoso District. The need for rice is increasing every year. Rice production is inseparable from paddy production in the field. Paddy production on the field will be optimal if the variety matches the soil and land characteristics. This research is an exploratory study to evaluate the suitability of the typical location of paddy varieties in Tegalampel Sub-District, Bondowoso District. The research was conducted in August-December 2020 in Tegalampel District, Jember Regency, and soil analysis at the Soil Fertility Laboratory of the University of Jember. The research method uses a survey method which is divided into 3 stages: literature study, field survey, and data analysis. The results showed Tegalampel Sub-District has the potential to be planted with paddy divided into 3 land uses with a height of <700 m asl with rainfall <2000 mm / year, namely irrigated rice fields, rain-fed rice fields, and dry fields / dry land. Suitability of rice varieties for irrigated rice fields namely Ciherang, Inpari 1, Inpari 6 Jete, Mekongga by 16.60%; suitability of rice varieties for rain-fed rice fields are varieties Inpari 10, Inpari 12, Inpari 13, Inpari 18, Inpari 19, Inpari 20, Inpari 38, Inpari 39, Inpari 40, Inpari 41, Dodokan, Silugonggo by 26.64%; and suitability of rice varieties for dry fields / dry land, namely Inpago 5, Inpago 8, Inpago 9, Inpago 10, Inpago 11, Inpago 12 by 26.35%.